Neurotrophic factor alpha 1 gene therapy in Alzheimer’s disease: scope and advancements - Shaikh, Ammara; Ahmad, Fairus; Teoh, Seong Lin; Kumar, Jaya; Yahaya, Mohamad Fairuz (Frontiers in Molecular Neuroscience, 2025)
Alzheimer’s disease (AD) is the leading cause of dementia, accounting for 60–80% of all cases globally. Hallmark pathologies of AD include the accumulation of amyloid β peptide and phosphorylated tau, leading to neuronal circuit dysfunction, defective axonal transport, and neurotransmitter system (NTS) abnormalities. Disruptions in acetylcholine, GABA, dopamine, serotonin, and glutamate levels, as well as the loss of cholinergic, GABAergic, and monoaminergic neurons, contribute to the progression of AD. Additionally, neurotrophic factors like brain-derived neurotrophic factor (BDNF) and nerve growth factor (NGF) are significantly reduced in AD, impacting neuronal health and synaptic integrity. This review highlights the emerging role of neurotrophic factor alpha 1 (NF-α1), also known as carboxypeptidase E, in AD. NF-α1 shows neuroprotective and neurogenesis-promoting properties, offering potential for therapeutic interventions. The review compares NF-α1 gene therapy with other neurotrophin-based treatments, providing insights into its efficacy in AD management.